2021
DOI: 10.7554/elife.62236
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human glucocorticoid response markers using integrated multi-omic analysis from a randomized crossover trial

Abstract: Background:Glucocorticoids are among the most commonly prescribed drugs, but there is no biomarker that can quantify their action. The aim of the study was to identify and validate circulating biomarkers of glucocorticoid action.Methods:In a randomized, crossover, single-blind, discovery study, 10 subjects with primary adrenal insufficiency (and no other endocrinopathies) were admitted at the in-patient clinic and studied during physiological glucocorticoid exposure and withdrawal. A randomization plan before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 92 publications
2
24
0
Order By: Relevance
“…We found that the ratio of transcriptome regulated by GC depended on tissue type. Our results were in line with previous findings that in skin a relatively smaller gene set (6.3%) while in adipose tissue, brain and peripheral blood mononuclear cells a larger gene set (10–20%) were regulated by GC, [ 21 , 58 , 65 , 66 ]. Interestingly, in the liver GC induced vast transcriptional responses, with more than 30% of genes being regulated [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the ratio of transcriptome regulated by GC depended on tissue type. Our results were in line with previous findings that in skin a relatively smaller gene set (6.3%) while in adipose tissue, brain and peripheral blood mononuclear cells a larger gene set (10–20%) were regulated by GC, [ 21 , 58 , 65 , 66 ]. Interestingly, in the liver GC induced vast transcriptional responses, with more than 30% of genes being regulated [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, in a recent article, miR-122-5p was identified as a possible link between nonphysiological (externally administered) GCs and the effects caused by GC administration. Additionally, the measurement of miR-122-5p expression can be a potential marker to monitor appropriate glucocorticoid activity and to avoid overtreatment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been associated with decreased expression of the hormone-stimulated enzymes regulating the fat mobilization process [30] and has been related to insulin resistance and obesity. Fatty acids related to triglyceride metabolism (e.g., palmitic, stearic, linoleic) have been associated with glucocorticoid action in two recent untargeted metabolomic studies of the dose-dependent effect of glucocorticoid treatment of glucocorticoid-dependent disorders [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Hypernetwork analysis was performed to investigate higher order interactions between target genes, a general model of which is outlined in Supplementary Figure 1 30 . All analyses were performed in R (version 3.4.2).…”
Section: Hypernetwork Modellingmentioning
confidence: 99%
“…This hypernetwork adjacency matrix represents the higher order interactions between pairs of genes in a manner not captured by traditional transcriptomic approaches. As a measurement of co-ordination, hypernetworks have been suggested to model functional relationships 30 . Coordination between age-related genes and the rest of transcriptome was investigated by interrogating the incidence matrix of the hypernetwork and identifying a subset of edges and nodes which could form a complete subgraph.…”
Section: Hypernetwork Modellingmentioning
confidence: 99%